Binary test design problem. (July 2018) - Turetsky, Vladimir; Steinberg, David M.; Bashkansky, Emil
Highlights: The problem of binary test planning is formulated. Different optimization criteria are proposed and explored. The problem is examined from the two extremities of test items amount. Abstract: Unlike in traditional measurement methods, in binary testing each test item provides only one bit of information. In view of limited test resources, effective planning of the test is crucial. In this article, the general problem is formulated from the metrological point of view for a high variety of objects under test and a homogeneous item response function. Different optimization criteria are reviewed for one-item testing (single and replicated), and their advantages and disadvantages are discussed. The article concludes with preliminary recommendations for how to plan a binary test.